(untitled) (Carte Romanze, 2021)
The small production of the trouvère Hue de la Ferté is undoubtedly one of the few examples of historico-political poetry in the Old-French lyrical panorama, and therefore is worthy of attention. The essay not only offers a new critical and explained edition, but also a new dating hypothesis, based on an accurate re-examination of the dating conjectures made so far. The resulting idea is that the three texts were written one close to the other, probably around the first semester of the 1230, as a part of one homogeneous project aiming on the one hand to discredit the enemies of the Baron’s party, on the other hand to glorify and express the values on which the party was constructed.